2020
DOI: 10.1002/jcla.23525
|View full text |Cite
|
Sign up to set email alerts
|

Serotypes, antibiotic resistance, and virulence genes of Salmonella in children with diarrhea

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited and is not used for commercial purposes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(40 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…25 , 27 Extended-spectrum cephalosporins, especially ceftriaxone, have previously been suggested as the drugs of first-line choice for treating children with serious nontyphoidal Salmonella infections. However, the drug resistance rates of ceftriaxone remained at a high level in the past ten years, which was significantly higher than Guangdong 12 and Hangzhou 14 in China. Therefore, the drug resistance of ceftriaxone in southwest China is alarming.…”
Section: Discussionmentioning
confidence: 93%
See 2 more Smart Citations
“…25 , 27 Extended-spectrum cephalosporins, especially ceftriaxone, have previously been suggested as the drugs of first-line choice for treating children with serious nontyphoidal Salmonella infections. However, the drug resistance rates of ceftriaxone remained at a high level in the past ten years, which was significantly higher than Guangdong 12 and Hangzhou 14 in China. Therefore, the drug resistance of ceftriaxone in southwest China is alarming.…”
Section: Discussionmentioning
confidence: 93%
“…Other studies in China also displayed that Salmonella Typhimurium was the most common serotype. 14 , 26 , 44 , 45 And Salmonella Typhimurium was also the most common serotype in North America and Oceania. 46 However, some other studies showed that Salmonella Enteritidis was the most common serotype in China.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Six pairs of antibiotic-resistant gene and eleven pairs of SPI1-6 virulence gene amplification primers were designed based on the gene sequences in GenBank and the literature (5,(11)(12)(13)(14)(15)(16)(17)(18). All PCR products were sequenced using primer walking, starting with 3CS and 5CS primers (Table 1).…”
Section: Determination Of Antibiotic Resistance Genes and Spi1-6 Genesmentioning
confidence: 99%
“…Salmonella is an important foodborne pathogen that causes acute diarrhea in humans worldwide 1 . In approximately 5%–10% of patients, the condition is further complicated by bacteremia, which can be life threatening.…”
Section: Introductionmentioning
confidence: 99%